Correlation between High Serum Uric Acid Levels with Occurrence of Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes - Mudjiani Basuki1, Muhammad Hamdan1, Fidiana1, Fadil1, Deasy Putri Sukarno1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Diabetic Peripheral Neuropathy is a chronic microvascular complication of type 2 diabetes mellitus (T2DM) leads to increased risk of foot ulceration and morbidity.The increased serum uric acid (SUA) levels have been linked to macro vascular disease in T2DM. We found that the correlation between SUA levels and diabetic peripheral neuropathy has not been investigated. Objective: To determine the correlation between high serum uric acid levels and diabetic peripheral neuropathy. Method: The case-control design was used in this study and the sampling was done consecutively by following the inclusion and the exclusion criteria. The diabetic peripheral neuropathy was evaluated using EMNG and the serum were taken for uric acid levels examination. Chi square test was used for data analysis. Results: Thirty subjects were enrolled and divided into an experimental group of 15 subjects and a control group of 15 subjects as well. We found that the diabetic peripheral neuropathy did not show a significant correlation with high serum uric acid levels, p=0,136 and OR 3,143 (CI 95% 0,681-14,503). Conclusion: High serum uric acid levels did not have correlation with diabetic peripheral neuropathy.